1996
DOI: 10.1111/j.1476-5381.1996.tb15606.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the hepatic α1‐adrenoceptor responsiveness by colchicine: dissociation of free cytosolic Ca2+‐dependent and independent responses

Abstract: 1 The cytoskeletal depolymerizing agent, colchicine, prevents the hepatic ax-adrenoceptor-mediated stimulation of respiration, H+ and Ca2+ release to the effluent perfusate, intracellular alkalosis, and glycogenolysis. Unlike the other parameters, colchicine does not perturb the a,-agonist-induced stimulation of gluconeogenesis or phosphorylase 'a' activation, and enhances the increase in portal pressure response. The lack of effect of colchicine on the hepatic a2-adrenoceptor-mediated effects indicates that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Furthermore, in agreement with our findings on colchicine-treated endothelial cells ( Figure 15B), this drug induced only very moderate effects on intracellular calcium in resting rat brain synaptosomes (72) or cerebellar granule cells (73). However, colchicine has been shown to modulate the calcium permeability of some ion channels in response to chemical stimulation (73)(74)(75). Perhaps colchicine may exert a similar effect on putative calcium channels on the nuclear envelope.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in agreement with our findings on colchicine-treated endothelial cells ( Figure 15B), this drug induced only very moderate effects on intracellular calcium in resting rat brain synaptosomes (72) or cerebellar granule cells (73). However, colchicine has been shown to modulate the calcium permeability of some ion channels in response to chemical stimulation (73)(74)(75). Perhaps colchicine may exert a similar effect on putative calcium channels on the nuclear envelope.…”
Section: Discussionsupporting
confidence: 90%
“…We have recently reported that activation of hepatic α " -adrenoreceptors is accompanied by activation of the Na + \H + exchanger, resulting in extracellular acidification and intracellular alkalinization [23,24,27]. In agreement with these reports, Figure 8 shows that activation of α " -adrenergic or angiotensin II receptors produced intracellular alkalinization in isolated hepatocytes (Figure 8, left-hand traces).…”
Section: Effect Of T 3 On Agonist-induced Intracellular Alkalinizationsupporting
confidence: 83%
“…Intracellular [Ca# + ] and pH were determined using the intracellular trappable fluorescent Ca# + and pH indicators fura 2 and 2h,7h-bis(carboxyethyl)-5,6-carboxyfluorescein (BCECF), respectively, [25,26]. Incubation, loading of the hepatocytes with fura2 acetoxymethyl ester or BCECF-AM and the measurements of agonistmediated changes in cytosolic free Ca# + levels and pH i were performed as described previously [24,27]. To measure Ca# + inflow, liver cells were depleted of internal Ca# + by incubation in nominally Ca# + -free medium in the presence of the endomembranes Ca# + -ATPase inhibitor, thapsigargin [28].…”
Section: Measurement Of Cytosolic Ca 2 + and Intracellular Phmentioning
confidence: 99%
“…Intriguingly, a study performed in a vascular smooth muscle cell line (AC01) (18) demonstrated that the ␣ 1D ARs, although representing the minor population compared with the ␣ 1B ARs in this cell, are the main mediators of phosphoinositide/Ca 2ϩ signaling. Moreover, based on their experimental data from isolated hepatocytes, Butta et al (45) concluded that there are at least two major ␣ 1 AR signaling pathways; one is PKC-dependent and independent of variations in free cytosolic Ca 2ϩ , and the other one is dependent on variations in free cytosolic Ca 2ϩ but is PKCindependent. Actually, the ability of ␣ 1 AR to activate CaMK has been previously realized.…”
Section: Discussionmentioning
confidence: 99%